Problems of legal regulation of bilingualism in UKRAINE - Гусар, О. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article highlights the issue of the historical development of Ukrainian and Russian languages in Ukraine. The author of the analysis of the legal framework on the regulation of bilingualismin the country.